Behind the scenes at JPAHS: perspective of the editorial assistants - Khanal, Inesh; Shrestha, Aakripa Rani; Chand, Amit; Neupane, Aastha; Bhatta, Rohit Raj; Shrivastab, Ritika (Journal of Patan Academy of Health Sciences, 2025)
Medical journals operate with rigorous editorial workflow to ensure that the published content is credible and ethically sound, but these processes and workflow remain largely opaque to the authors and readers. In this journology narrative, the editorial assistants at Journal of Patan Academy of Health Sciences (JPAHS) aim to describe how a manuscript travels from submission to publication, covering the initial screening, peer review process, communication between authors and editors, and production emphasizing on their role in all of this. Much of our role involves the invisible but essential work of ensuring manuscripts comply with journal standards, ethical principles, and international guidelines such as those set by Committee on Publication Ethics (COPE) and the International Committee of Medical Journal Editors (ICMJE).